2014
DOI: 10.5505/aot.2014.35744
|View full text |Cite
|
Sign up to set email alerts
|

Cyberknife® Stereotactic Radiosurgery for Pituitary Adenomas: Clinical Outcomes

Abstract: ÖZET Amaç:Rezidü ve/ veya nüks hipofiz adenomlarının tedavisinde stereotaktik radyocerrahi alternatif bir tedavi seçeneğidir. Bu yazıda kliniğimizde Cyberknife® stereotaktik radyocerrahi (SRC) uyguladığımız hipofiz adenomlu hastaların tedaviye yanıtlarının değerlendirilmesi amaçlanmıştır. Yöntemler: Dr. A.Y. Ankara Onkoloji Eğitim ve Araştırma Hastanesi Radyasyon Onkolojisi Kliniğinde, Ocak 2010-Haziran 2013 tarihleri arasında beşi fonksiyonel ve ikisi non-fonksiyonel olmak üzere toplamda yedi hipofiz adenomlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Avci et al reported the outcomes of 7 patients with PA treated with CyberKnife (10). In this study median follow-up period was 18 months (range 14-55 months) and the median dose was 22 Gy, given in 3 or 5 fractions.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Avci et al reported the outcomes of 7 patients with PA treated with CyberKnife (10). In this study median follow-up period was 18 months (range 14-55 months) and the median dose was 22 Gy, given in 3 or 5 fractions.…”
Section: Resultsmentioning
confidence: 74%
“…Shortly after the introduction of CyberKnife, PA treatment with CyberKnife began. After a while treatment results and side effects published in some articles (1, [3][4][5][6][7][8][9][10][11]. In these articles, various criterias were used to determine local control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation